Early cellular events and potential regulators of cellulase induction in Penicillium janthinellum NCIM 1366 - Christopher, Meera; Sreeja-Raju, Athiraraj; Abraham, Amith; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Scientific Reports, 2023)
Cellulase production by fungi is tightly regulated in response to environmental cues, and understanding this mechanism is a key pre-requisite in the efforts to improve cellulase secretion. Based on UniProt descriptions of secreted Carbohydrate Active enZymes (CAZymes), 13 proteins of the cellulase hyper-producer Penicillium janthinellum NCIM 1366 (PJ-1366) were annotated as cellulases- 4 cellobiohydrolases (CBH), 7 endoglucanases (EG) and 2 beta glucosidases (BGL). Cellulase, xylanase, BGL and peroxidase activities were higher for cultures grown on a combination of cellulose and wheat bran, while EG was stimulated by disaccharides. Docking studies indicated that the most abundant BGL- Bgl2- has different binding sites for the substrate cellobiose and the product glucose, which helps to alleviate feedback inhibition, probably accounting for the low level of glucose tolerance exhibited. Out of the 758 transcription factors (TFs) differentially expressed on cellulose induction, 13 TFs were identified whose binding site frequencies on the promoter regions of the cellulases positively correlated with their abundance in the secretome. Further, correlation analysis of the transcriptional response of these regulators and TF-binding sites on their promoters indicated that cellulase expression is possibly preceded by up-regulation of 12 TFs and down-regulation of 16 TFs, which cumulatively regulate transcription, translation, nutrient metabolism and stress response.